Patients' beliefs about medicines in a primary care setting in Germany - Mahler, Cornelia; Jank, Susanne; Haefeli, Walter E.; Szecsenyi, Joachim (Journal of evaluation in clinical practice, 2012)
Objectives The aim of this study was to explore patients' beliefs about medicines by administering the German version of the Beliefs about Medicines Questionnaire (BMQ) in a primary care setting among chronically ill patients and to examine its psychometric properties. The BMQ assesses patients' beliefs about their individual prescribed medication as well as their beliefs about medicines in general. Methods A cross-sectional survey of 485 chronically ill patients was performed. The German version of the BMQ was evaluated in terms of internal consistency, validity and scale structure. To assess validity the Medication Adherence Report Scale (MARS-D) and the Satisfaction with Information about Medicines Scale (SIMS-D) were applied. Results The BMQ showed good internal consistency (Cronbach's α 0.79-0.83). Patients' belief about the specific necessity of their medicines correlated positively with the MARS-D (ρ = 0.202; P < 0.01). There were significant correlations in the predicted direction between the MARS-D and all the BMQ subscales with the exception of the General-Overuse subscale (ρ = −0.06; P = 0.30). Relationship to the SIMS-D was comparable to the original study. Factor analysis corroborated the scale structure. Conclusions The BMQ is a suitable instrument to measure patients' beliefs in medicines in German primary care settings. Most patients in our sample had positive beliefs concerning the necessity of their medication. Their levels of concern were associated with higher non-adherence.